The legal order of the algorithm: the regulatory function of law and the ordering function of the algorithm (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
Humans have historically developed tools, both tangible and intangible, to impose order, mitigate risks, and align actions with collective values. This article explores the parallel roles of legal norms and algorithms in establishing regularities that may be beneficial to human cognition, shielding it from boundless unpredictability. With an emphasis on the intertwining of rational and emotional facets of human cognition, we delve into the shared ordering functions of law and AI algorithms. The article highlights the challenges, biases, and dilemmas surrounding AI and its regulation. We conclude by advocating for a more structured political approach to AI governance, emphasizing the importance of delineating roles for AI to ensure certain domains remain exclusively within human purview.
Keywords: Legal rules; algorithmic rules; human biases; machine biases; european risk based approach; algorithmic sovereignty; human sovereignty